Saúde mental na estratégia saúde da família : estudo sobre as competências de enfermeiros - Martins, Álissan Karine Lima (2014)
Mental health care, in accordance with public health policies, underwent an intense process of restructuring care practices starting to include it in the Primary Health Care space. For proper performance facing the demands on mental health in this new scenario, the nurses of the Family Health Strategy should be prepared to adopt behaviors grounded in knowledge, skills, and attitudes consistent with everyday situations. In this context, this study aimed to evaluate the skills of nurses of the Family Health Strategy to work in mental health. A methodological research of quantitative approach conducted with 149 nurses in the basic health units of municipalities in the 20th and 21st Regional Health Coordinators of the State of Ceará, Brazil. For data collection, we developed a scale, validated by judges and applied with the nurses of the Family Health Strategy from September to October 2013. To assess the reliability of the scale, we applied the Cronbach’s alpha. For content validity, we used the Content Validation Index (CVI). We used descriptive statistical analysis calculated by percentages of socio-educational variables, besides measures of central tendency, such as mean and standard deviation of the categories of the scale. We performed the analyses by comparing means through the Student’s t-test and Snedecor’s F distribution, together with analyzes of associations and correlations of skills with the characteristics of nurses by means of Chi-square nonparametric tests. For all inferential statistical analyzes, we established the level of significance of 5%. Regarding ethical issues, we followed the rules of Resolution 466/2012. According to the committee of judges, results showed that the content of the scale was comprehensive and valid. For content validity, the CVI scale was 0.86. The Cronbach’s alpha was 0.91, indicating excellent reliability. In the sample, there was a predominance of females (87.2%), married/in stable relationship (59.7%), and aged 30-39 years (51.7%). The items that presented the highest levels of agreement among the nurses were associated with the skill in the nurse-patient therapeutic relationship, of management and negotiation of supply of care within the health system for monitoring and assurance of health care practice. Regarding the connection between the scale and the socio-demographic and training characteristics, there was association in age and function skills of teaching-orientation (p=0.034) and cultural skills (p=0.044); training time and function skills of teaching-orientation (p=0.002) and monitoring and guarantee of health care practice (p=0.044); and time of performance and skills of teaching-orientation (p=0.006). Considering the total scale, the highest scores were found among female workers (98.4 ± 16.7), aged 45-60 years (101.9 ± 21.7), with more than 10 years of training (99.4 ± 19.1), and work experience in PHC (99.4 ± 19.1). Thus, we hope the study results contribute to directing actions for qualification in mental health practice within Primary Health Care.